Cycle systems in the complete bipartite graph plus a one-factor - Ling, San (2012)
Let Kn,n denote the complete bipartite graph with n vertices in each partite set and Kn,n+I denote Kn,n with a one-factor added. It is proved in this paper that there exists an m-cycle